PERBEDAAN FINANCIAL PERFORMANCE PASCA SECONDARY OFFERINGS - Djaja Perdana; Herbowo Herbowo (Akademi Akuntansi YKPN Yogyakarta, 2019)
This study aims to examine the differences in corporate financial performance before and after secondary offerings. The financial performance is proxied by WCR, DER, Solvency, ROA, ROE, Asset Turnover (ATO) and Growth ratio which representing the value of liquidity, financing, activity, performance and growth of the firm. The study involved 67 samples of the companies listed on the Indonesia Stock Exchange conducting secondary offerings during 2008-2013 period and selected through purposive random sampling method and using Financial Statement data from 2005-2016 period. Hypothesis test is performed using Wilcoxon Signed Rank test. The results of this study indicate that there is no significant difference in the ratio of Solvency, ROA and ROE between before and after secondary offerings, but there are significant differences in the ratio of WCR, DER, Asset Turnover and Growth. WCR ratio after secondary offerings increased, while DER ratio after secondary offerings decreased, the condition of both ratios showed better performance. While the indication of poor performance seen in decreasing asset turnover ratio and growth ratio.Keywords : agency theory, financial performance, secondary offerings